Four new species of Cymatodera Gray from Mexico (Coleoptera, Cleridae, Tillinae) - Burke, Alan F.; Zolnerowich, Gregory (My University, 2014)
Four new species of Cymatodera from Mexico: Cymatodera bogcioides sp. n.; Cymatodera pueblae sp. n.; Cymatodera mitae sp. n.; and Cymatodera lineata sp. n. are described based on adult male and female specimens. Male genitalia and other characters of taxonomic value are presented.
Keywords: Cymatodera; Terminalia; Antennae; Genitalia; Mexico; Checkered beetle